Passivity-Based Tracking Control of a Mobile Manipulator Robot - Ikni, Samir; Achour, Abdelyazid (International Journal of Integrated Engineering, 2023)
This work presents a control approach based on the passivity principle, developed to guarantee performance of the application used to track the trajectory of mobile manipulator when disturbed. By exploiting the particularity of the mobile manipulator robots modelling equipped with a nonholonomic mobile base, we present a global control law for the mobile manipulator as a single system. This control allows taking into account the whole system and modifying its dynamics by introducing a highly non-linear regressor matrix to consider uncertainties and modeling constraints. The presented controller is applied to the mobile manipulator robot composed of a manipulator’s arm with 2 DDL mounted on a mobile unicycle platform. Simulation tests validate the performance of the proposed approach when external disturbances occur; showing an acceptable performance of the system’s stability and validated by exploiting the Lyapunov theory.